A kinematics recommendation for trunk stability and control assessments during unstable sitting. (November 2019) - Roberts, Brad W.R.; Vette, Albert H.
Highlights: A range of kinematics have been used to assess trunk control in unstable sitting. The kinematics characterizing task completion in unstable sitting are unknown. We compared base of support and body angular kinematics during unstable sitting. The trunk remains quasi-static and is stabilized via motion of the base of support. Unstable sitting studies should include the analysis of base of support kinematics. Abstract: Trunk control has been commonly studied via an unstable sitting paradigm, with the majority of analyses using angular kinematics-based, posturographic measures. However, considerable variability in the choice of kinematics exists. Furthermore, the kinematics capturing the completion of this task are unknown. The purpose of this study was to characterize the kinematics in unstable sitting by quantifying and comparing the angular motion of the base of support, pelvis, and trunk as elicited via a commonly used wobble board (WB) paradigm. WB, pelvis, and trunk motion was recorded in fifteen non-disabled participants sitting on a wobble board. Posturographic measures were calculated and compared between corresponding WB and pelvis, and between WB and trunk angles. The trunk was stabilized through relatively large WB motion, with the trunk adopting a quasi-static pose. For all measures, angles, and conditions, the WB measure values were significantly larger than their corresponding pelvis or trunk values. Our findings demonstrate that the WB-human system is stabilized by regulating WB motion. Future work utilizing an unstable sitting surface and kinematics-based analyses to investigate trunk control should include the analysis of base of support kinematics.